The Influence of the TGT (Teams Games Tournament) Learning Model Based on Deep Learning on Science and Social Studies (IPAS) Learning Outcomes in Third-Grade Elementary School - Elysia, Sarah Masyitha; Atmojo, Idam Ragil Widianto; Matsuri, Matsuri (Universitas Sebelas Maret, 2026)
Low learning outcomes in IPAS among third-grade elementary school students are often caused by conventional teaching approaches that lack depth and active engagement. This study aims to determine the effect of the Teams Games Tournament (TGT) learning model based on deep learning approach on third-grade students' IPAS learning outcomes. This research is a quasi-experiment using a non-equivalent control group design, involving two classes from Cluster 2 UPT SD Negeri Gresik, each consisting of 25 students. The experimental class implemented TGT with deep learning through a monopoly game on money needs, while the control class used conventional learning; data were collected via pretest and posttest, analyzed using independent t-test and N-gain in Jamovi. Results showed the experimental class posttest average was significantly higher (p < 0.05), N-gain reached moderate to high categories, and mastery exceeded 80%. Thus, TGT based on deep learning positively and significantly improves IPAS learning outcomes.